The Influence of Workload on Employee Performance Through Employee Satisfaction as an Intervening Variable (A Study at PT Perusahaan Listrik Negara (PLN) (Persero) Gardu Transmission Service Unit (ULTG) Panakkukang, Makassar City) - Al Anshori N, Muh Fadhil; Burhanuddin, Burhanuddin; Aswar, Nurul Fadilah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to examine and analyze the influence of workload on employee performance, with employee satisfaction as an intervening variable at PT Perusahaan Listrik Negara (PLN) (Persero) Gardu Transmission Service Unit (ULTG) Panakkukang, Makassar City. Using a quantitative approach, data were collected through questionnaires distributed to employees and analyzed using path analysis techniques. The results show that workload has a significant negative effect on employee satisfaction. Furthermore, employee satisfaction has a significant positive effect on employee performance. The findings also indicate that workload indirectly affects employee performance through the mediating role of employee satisfaction. These results suggest that managing employee workload and improving satisfaction are crucial strategies to enhance overall performance within the organization.